Features of investment in economies with different level of development: The role of infrastructure projects financing (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The role of infrastructure investment is increasingly critical in both developed and transitional economies due to its wide-ranging multiplier effects, including capital inflows, production growth, and enhanced transport efficiency. This article aims to examine the significance of infrastructure investments across these economic contexts. Using a comparative and structural analysis of infrastructure investment from 1990 to 2023, the study highlights key regional differences across Europe, Central Asia, East Asia, and the Pacific. These variations are influenced by factors such as institutional capacity, urbanization levels, population density, infrastructure needs, export potential, and budget constraints. Political and regulatory frameworks for attracting public and private investment significantly shape capital allocation strategies. In East Asia and the Pacific, investment is primarily directed toward new transport infrastructure through greenfield projects and mixed financing models. Conversely, Europe and Central Asia focus on modernizing existing infrastructure through pragmatic and balanced investment policies, often influenced by national financial strategies. The findings offer practical value by demonstrating how the experiences of developed economies can inform infrastructure strategies in transitioning countries, promoting more efficient investment practices and long-term development planning. These insights are particularly relevant for policymakers seeking to optimize infrastructure growth within their specific economic and institutional contexts.
Keywords: Infrastructure; Infrastructure investments; Investments; Public-private partnerships; Transport